Lercanidipin chylous peritonitis - Hanene Gaied; Maan Joseph (RDPLF, 2018)
We report a case of lercanidipin-induced chylous peritonitis (CP) occurring in a patient undergoing continuous ambulatory peritoneal dialysis (CAPD), a 22-year-old male with chronic renal failure with indeterminate nephropathy.. The patient presented a turbid drainage fluid at the start of peritoneal dialysis (PD). The chyloperitoneum resolved after stopping lercanidipin without recurrence. Lercanidipin induced-chyloperitoneum is a rare complication in PD. It is a benign form of non-infectious peritonitis that can be confused with an infectious peritonitis. The most common causes of CP are infectious, obstructive and abdominal malignancy. This paper discusses the possible causes of CP, the physiopathology and the management of lercanidipin-induced chyloperitoneum.